2015
DOI: 10.1590/s1984-29612015062
|View full text |Cite
|
Sign up to set email alerts
|

Development and health status of Centropomus undecimalisparasitized by Rhabdosynochus rhabdosynochus (Monogenea) under different salinity and temperature conditions

Abstract: Development and health status of AbstractThis study evaluated the correlation of hematological parameters with the mean abundance of the monogenean helminth Rhabdosynochus rhabdosynochus in Centropomus undecimalis reared at different temperatures and salinities. The experimental conditions were: 28 °C/0 ppt (parts per thousand); 28 °C/15 ppt; 28 °C/32 ppt; 25 °C/0 ppt; 25 °C/15 ppt; and 25 °C/32 ppt. The prevalence was 100.0% in fish at 28 °C/15 ppt, 28 °C/32 ppt and 25 °C/15 ppt, which was significantly diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
0
7
0
2
Order By: Relevance
“…Nevertheless, even though at a slow rate, recent efforts have been undertaken to depict the diversity of this group in South American fish (fig. 1; Vieira et al , 2009; Arredondo & Gil de Pertierra, 2010, 2012; Lanfranchi & Timi, 2011; Braicovich et al ., 2014; Lisitsyna et al ., 2015; Mello et al ., 2015).…”
Section: Taxonomy and Systematics Of The Helminths Parasitic In Fish mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, even though at a slow rate, recent efforts have been undertaken to depict the diversity of this group in South American fish (fig. 1; Vieira et al , 2009; Arredondo & Gil de Pertierra, 2010, 2012; Lanfranchi & Timi, 2011; Braicovich et al ., 2014; Lisitsyna et al ., 2015; Mello et al ., 2015).…”
Section: Taxonomy and Systematics Of The Helminths Parasitic In Fish mentioning
confidence: 99%
“…Just a few researchers are currently working on this subject. In Brazil two groups can be cited: one from the EMBRAPA, State of Amapá (Soares et al , 2016), and one from the Department of Aquiculture of the UFSC, State of Santa Catarina (Mello et al ., 2015; Hashimoto et al ., 2016).…”
Section: Current Research Groups and Their Geographic Distributionmentioning
confidence: 99%
“…2e) is the fastest-growing snook species and, together with the fat snook (Centropomus parallelus), is the most cultivated species under experimental conditions (Alvarez-Lajonchère and Tsuzuki 2008). They are diadromous, euryhaline, stenothermic and estuarine-dependent fish found in rivers, estuaries and coastal lagoons and along rocky shores (Mello et al 2015;Pope et al 2006). Studies have demonstrated that snooks have high osmoregulatory capacity, which allows them to maintain their internal osmotic pressure practically independent of external salinity concentrations (0-40 ppt) and to be produced in fresh water (Michelotti et al 2018;Liebl et al 2016;Gracia-López et al 2006).…”
Section: Snook (Centropomus Sp)mentioning
confidence: 99%
“…Durante 42 dias, foram avaliados dois tratamentos, em triplicata, diferenciados entre si pela utilização de duas rações comerciais distintas (Tabela I): Ração A, formulada para peixes carnívoros de água doce, e Ração B, utilizada na larvicultura de peixes marinhos em laboratório. Para isso, dois sistemas independentes e idênticos de recirculação de água foram utilizados, cada um com três tanques de 200 L conectados a um macrocosmo de 150 L. Em ambos os macrocosmos havia filtros mecânico e biológico, carvão ativado, bomba para o retorno da água (Atman®, PH 3500) e termostato-aquecedores (Atman®, 300 W), como descrito por Mello et al (2015).…”
Section: Delineamento Experimentalunclassified
“…Aliado a isso, o correto manejo alimentar é fundamental para alcançar taxas ideais de crescimento e atender aos demais índices zootécnicos de interesse produtivo (ex. rendimento de filé), podendo auxiliar também na manutenção do estado de saúde dos peixes em confinamento (Mello et al, 2015), o que reforça a necessidade de mais estudos nessa área.…”
Section: Introductionunclassified